2016
DOI: 10.1007/s10570-016-0963-5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of thermally stable cellulose nanocrystals via a sustainable approach of FeCl3-catalyzed formic acid hydrolysis

Abstract: Cellulose nanocrystals (CNCs) can be used as building blocks for the production of many renewable and sustainable nanomaterials. In this work, CNCs were produced from bleached eucalyptus kraft pulp with a high yield over 75 % via FeCl 3 -catalyzed formic acid (FA) hydrolysis process. It was found that the particle size of resultant CNC products (F-CNC) decreased with the increase of FeCl 3 dosage in FA hydrolysis, and a maximum crystallinity index of about 75 % could be achieved when the dose of FeCl 3 was 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
87
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 150 publications
(91 citation statements)
references
References 79 publications
2
87
0
Order By: Relevance
“…For example, the yield of CNCs could reach to 75.6% when 58 wt.% sulfuric acid was used at 56 ∘ C for 210 min [56]. CNCs from sulfuric acid hydrolysis have poor thermal stability due to the sulfate group which is a significant barrier for thermal process in composites [63]. The thermal stability of CNCs can be improved through neutralization with NaOH [58,64,65].…”
Section: Mineral Acid Hydrolysismentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the yield of CNCs could reach to 75.6% when 58 wt.% sulfuric acid was used at 56 ∘ C for 210 min [56]. CNCs from sulfuric acid hydrolysis have poor thermal stability due to the sulfate group which is a significant barrier for thermal process in composites [63]. The thermal stability of CNCs can be improved through neutralization with NaOH [58,64,65].…”
Section: Mineral Acid Hydrolysismentioning
confidence: 99%
“…The results showed that the CNCs modified by TEMPO have much higher crystalline and much more surface charge. In order to further increase the hydrolysis efficiency, Du et al introduced the FeCl 3 to the FA system [63]. Figure 4 shows the process flow and the CNCs were obtained from bleached eucalyptus kraft pulp with a high yield (75%).…”
Section: Organic Acid Hydrolysismentioning
confidence: 99%
“…Although, sulphuric acid is the most extensively used to afford the isolation of CNCs, other acids, such as phosphostungstic [19] , bromic, phosphoric [20] acid and organic acids (maleic [21], formic [22,23] and oxalic acid) were also reported for such purpose.…”
Section: Bacterial Cellulose (Bnc)mentioning
confidence: 99%
“…Among them, cellulose nanofibrils (CNFs)‐based films have attracted remarkable attention for the controlled drug release, because CNFs have high aspect ratio, excellent mechanical properties, good biodegradability, and good cytocompatibility ,. Moreover, the large amounts of hydroxyl or carboxyl groups are present on the surface of CNFs, which are appropriate for the formation of hydrogen bonds with hydrophilic drugs . Biocompatibility is an important performance of the materials when used in drug application.…”
Section: Introductionmentioning
confidence: 99%